Short-Term Effect of Vermicompost Application on Biological Properties of an Alkaline Soil with High Lime Content from Mediterranean Region of Turkey - Ilker Uz; Ismail Emrah Tavali (The Scientific World Journal)
This study was conducted to investigate direct short-term impact of vermicompost on some soil biological properties by monitoring changes after addition of vermicompost as compared to farmyard manure in an alkaline soil with high lime content from semiarid Mediterranean region of Turkey. For this purpose, mixtures of soil and organic fertilizers in different doses were incubated under greenhouse condition. Soil samples collected in regular intervals were analyzed for biological parameters including dehydrogenase, β-glucosidase, urease, alkaline phosphatase activities, and total number of aerobic mesophilic bacteria. Even though soil dehydrogenase activity appeared to be dose-independent based on overall evaluation, organic amendments were found to elevate dehydrogenase activity when sampling periods are evaluated individually. β-glucosidase, urease, alkaline phosphatase activity, and aerobic mesophilic bacterial numbers in vermicompost treatments fluctuated but remained significantly above the control. A slight but statistically significant difference was detected between organic amendments in terms of urease activity. Vermicompost appeared to more significantly increase bacterial number in soil. Clearly, vermicompost has a potential to be used as an alternative to farmyard manure to improve and maintain soil biological activity in alkaline calcareous soils from the Mediterranean region of Turkey. Further studies are needed to assess its full potential for these soils.